2013
DOI: 10.1021/ic400832h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Generation of Uniform Spherical LaMnO3, LaCoO3, Mn2O3, and Co3O4 Nanoparticles and Their High Catalytic Performance for Carbon Monoxide and Toluene Oxidation

Abstract: Uniform hollow spherical rhombohedral LaMO3 and solid spherical cubic MOx (M = Mn and Co) NPs were fabricated using the PMMA-templating strategy. Hollow spherical LaMO3 and solid spherical MOx NPs possessed surface areas of 21-33 and 21-24 m(2)/g, respectively. There were larger amounts of surface-adsorbed oxygen species and better low-temperature reducibility on/of the hollow spherical LaMO3 samples than on/of the solid spherical MOx samples. Hollow spherical LaMO3 and solid spherical MOx samples outperformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(59 citation statements)
references
References 75 publications
0
58
1
Order By: Relevance
“…Here we show that monophasic rare-earth cobaltite materials can be obtained by MWassisted synthesis within 30 minutes with massive time and energy savings. LaCoO3 has been synthesized previously by innovative and novel chemical synthesis methods [28][29][30], including MW-assisted processes [11,31,32], but the rest of the series (RE = Pr -Dy) has not been prepared before using MW heat sources to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Here we show that monophasic rare-earth cobaltite materials can be obtained by MWassisted synthesis within 30 minutes with massive time and energy savings. LaCoO3 has been synthesized previously by innovative and novel chemical synthesis methods [28][29][30], including MW-assisted processes [11,31,32], but the rest of the series (RE = Pr -Dy) has not been prepared before using MW heat sources to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Other effects of silica NPs include ROS generation, the production of IL-6, IL-8, MCP-1, TNF-α, IL-1β, and the enhanced expression of CD106, CD62E and tissue factor in human endothelial cells and monocytes. These suggest that interactions between particles, endothelial cells and monocytes may trigger or exacerbate cardiovascular dysfunction, atherosclerosis and thrombosis (Liu et al, 2012). Silica NPs affect inflammatory response in dendritic cells by activating p38 and NF-κB.…”
Section: Non-metal Oxide Nanoparticlesmentioning
confidence: 99%
“…The high reactivity of MnO x towards VOCs abatement is generally ascribed to easy variation of manganese oxidation state (Mn 2+ , Mn 3+ , Mn 4+ ), oxygen storage capacity in the crystalline lattice and high mobility of lattice oxygen [26]. Kim [29,30] and MnO 2 [28] were also previously investigated separately by different research teams for toluene oxidation. F. Wang et al [31] reported on the external morphology effect of MnO x (rod-, wire-, tube-, and flower-like morphologies) for the oxidation of toluene.…”
Section: Mno X In Catalytic Oxidation Of Toluenementioning
confidence: 99%